Report on the application of the principles recommended by the Judicature Commission to the Irish County Courts - Molloy, Constantine (Statistical and Social Inquiry Society of Ireland, 1874)
Since the subject of this report was entrusted to me, the principles recommended by the Judicature Commission has received the sanction of the Legislature, and become the law; and the year that has just now closed will always form a memorable epoch in the legal history of the Empire, signalized as it has been by the accomplishment, in a single session of parliament, of one of the most beneficial legal reforms ever effected. The fusion of legal and equitable principles, the simplification of law, and the preference for equitable principles over ancient statutes and harsh rules secured for England by the Judicature Act of 1873, must produce an improvement in the administration of justice, the importance of which it would be difficult to over estimate.
Read before the Society, 27 January 1874
Keywords: Legal reform; Equity in the Irish legal system; Judicature Commission to the Irish County Courts; 314.15